Biologics in severe asthma: the overlap endotype - opportunities and challenges. (1st December 2020) - Bakakos, A; Loukides, S; Usmani, O S; Bakakos, P
ABSTRACT: Introduction: Patients with severe asthma experience a significant burden of symptoms, disease exacerbations and medication side-effects. Severe asthma interferes with the patients' quality of life and has high health-care costs. New targeted biologic therapies have improved the management of severe asthma by significantly reducing exacerbations and maintenance corticosteroid use, and also improving lung function and patient quality of life. Areas covered: Not all severe asthmatics are eligible for such therapies. Those with allergic and eosinophilic asthma, usually referred to as 'T2-high' asthma benefit from anti-IgE and anti-IL-5/5 R antibodies respectively, whereas some asthmatics are eligible for both: 'overlap' endotype. In this review, we present briefly the monoclonal antibodies that have been approved in the management of severe asthma and we focus on the 'overlap' endotype. Expert opinion: Since these therapies are costly, it is extremely important to choose the right treatment for the right patient especially in the 'overlapping' one. The decision is mainly based on the judgment of the clinician and is often driven by the most easily obtainable biomarker, thus the blood eosinophil count. Comorbidities, patient's input and administration frequency may aid the decision of choosing one over another biologic.